Development of a centralized, remote clinical pharmacy service to enhance primary care - Rachel J. Finkelstein; Christopher P. Parker; Barcey T. Levy; Barry L. Carter; Korey Kennelty (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
More than 50% of Americans possess at least one chronic condition and another 25% suffer from two or more, leaving primary care teams tasked to care for the chronic, acute, and preventive care needs of their large patient panels. Pharmacists can reduce the burden on busy providers by effectively managing chronic diseases as members of health care teams. Many private physician practices lack the resources to include pharmacists on their teams. A centralized, remote clinical pharmacy services model allows pharmacists to remotely manage chronic disease in patients in collaboration with primary care providers. The purpose of this report is to describe how a centralized, remote clinical pharmacy team was developed, trained, and effectively integrated into multiple, diverse primary care settings across the U.S.